Effects of instream wood reintroduction on transport and storage processes in a lowland sandy stream - Howard, Ben Christopher; Baker, Ian; Buytaert, Wouter; Drummond, Jen; Kettridge, Nicholas; Ullah, Sami; Krause, Stefan (Frontiers in Earth Science, 2025)
The reintroduction of instream wood is a common technique to restore degraded streams, for example to reinstate transport and storage processes - primary controls of the movement of water, solutes, and particulates through the stream corridor - with the aim of initiating a shift towards a more natural or sustainable state. In the United Kingdom, this kind of restoration occurs predominantly in lowland sandy streams, yet to date no study has explicitly investigated its effects on transport and storage processes in such contexts. Here, we used a before-after-control-impact (BACI) experiment to test the effects of reintroducing instream wood on transport and storage processes in a lowland sandy stream under a range of stream discharges (Q), with an average of 0.0079 m3/s. In the restored reach, as compared to the control reach, the average hydraulic retention time increased by 27.6%, the average transient storage increased by 28.4%, and the residence time therein increased by 13%. Although these differences were not statistically significant, we attribute this to the inevitable large variability of field tests compared to controlled laboratory environments. We interpret the observed changes as an indication of a potential increase to transient storage overall but limited subsurface transient storage, especially during higher Q conditions. Overall, our results suggest limited effects of instream wood reintroduction on transport and storage processes in a lowland sandy stream, but also highlight challenges in evidencing such effects. Given the sensitivity of transport and storage processes to environmental setting, it may be challenging to predict the effects of restoration based on a small set of conditions or generalizations.